Debt Management and Monetary Policy: Interrelationships (Socio-Economic Development Panorama, 2008)
Macroeconomic prudence and stability become the building-blocks for sustaining an environment that supports higher   levels of saving, investment, exports, and economic growth. To foster such a macroeconomic framework, implementation of sound fiscal and monetary policies would constitute the major strategy. Sustainable level of fiscal deficit built on an outlook of improved revenue mobilization helps minimize the probable risks  and challenges attributable to the fiscal side. Debt servicing implications of excessive debt would lead to external sector vulnerabilities, even leading to the external sector as well as the macroeconomic crisis, thereby seriously jeopardizing the self-sustained economic growth process. On account of the different sources of government debt financing like the central bank, commercial banks and the other private entities including the individuals, the monetary implications are varied. Hence, while mobilizing debt resources, care should be exercised through assessing the related monetary impacts so as to improve  the monetary policy prudence. Because of the strong interlinkages between the fiscal and monetary aggregates, coordinated implementation of the policies would make their interrelationships more favorable for macroeconomic prudence and sustainability. A balanced level of fiscal deficit would provide the financial market the necessary short-term debt instruments (treasury bills) the open market operations in which would help attain the monetary policy objective by influencing the liquidity and the related indicators in the financial market. So, debt management and monetary policy conduct are strongly interlinked, necessitating proper management of the public debt for the effectiveness of the monetary policy management. Socio-Economic Development Panorama Vol.1(1) 2007 pp.67-75